The Transformation of Tablighi Jamaat's Da'wah: Digital Adaptation and Political Engagement in Indonesia - Hasanah , Umdatul; Holilah, Ilah; Saeful Milah, Aang; Halimatusa’diah, Halimatusa’diah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This research examines the evolving da'wah dynamics among Tablighi Jamaat adherents in Indonesia. Founded by Muhammad Ilyas Al-Kandahlawi in India in 1926, this transnational movement has significantly impacted Indonesia's Islamic landscape through systematic propagation practices including khuruj (preaching journeys), jaulah (local rounds), and chillah (40-day periods). The movement's da'wah methodologies are rooted in Jamaat tradition, transmitted through written texts, particularly Fadhailul A'mal, and oral bayan (lectures) by amirs (leaders). This investigation addresses a scholarly gap by uncovering transformative shifts in Tablighi Jamaat's da'wah practices—previously underexplored areas that reveal how traditional Islamic missionary methods adapt to contemporary Indonesian contexts while maintaining doctrinal authenticity. Using qualitative analysis, this study demonstrates that da'wah exhibits inherent dynamism, evolving alongside cultural and civilizational advancements. This dynamism is evident in Tablighi Jamaat's traditions, where the movement maintains strict adherence to core principles while implementing modifications in practical application methods.The findings reveal notable conceptual adaptability in how current followers execute da'wah activities, representing a balance between preserving traditional methodology and responding to contemporary challenges. This adaptability demonstrates the movement's capacity to navigate modern contexts without compromising fundamental beliefs. The study contributes new insights into the intersection of traditional Islamic practices and contemporary Indonesian society, showing how religious movements maintain authenticity while embracing necessary adaptations. However, the research acknowledges methodological limitations and restricted thematic scope, indicating areas requiring further exploration in future research endeavors to fully understand these complex transformation processes.